Assessing the Impact of Service Quality, Perceived Price, and Store Location on Customer Satisfaction in the Beauty Retail Sector: A Case Study of Soappahollic - Tambunan, Damelina Basauli; Thyrza Farizah Yosina; Teofilus (SKeTsa Bisnis (e-jurnal), 2025)
Introduction: This study investigates the influence of service quality, perceived price, and location on customer satisfaction in the context of Soappahollic, a beauty retail business. While prior research has examined these variables individually, limited attention has been given to their combined effects in the beauty retail sector. This research aims to address this gap by analyzing how these three factors simultaneously shape customer satisfaction. Method: The study adopts a quantitative approach using a survey design. Data were collected from 200 Soappahollic customers through simple random sampling. The collected data were analyzed using Structural Equation Modeling with the SmartPLS software to evaluate the relationships among service quality, perceived price, location, and customer satisfaction. Result: The analysis revealed that all three independent variables significantly influence customer satisfaction. Specifically, service quality (p = 0.004), perceived price (p = 0.0097), and location (p = 0.0458) were found to have a positive and statistically significant effect. Among these, service quality emerged as the most dominant factor contributing to customer satisfaction. Conclusion: The findings highlight the critical role of integrating high service quality, fair pricing strategies, and strategic store location in enhancing customer satisfaction and loyalty. This study provides practical insights for managers in the beauty retail industry to design more effective customer service strategies and contributes to the literature by emphasizing the interconnected impact of these variables in a retail setting